Barriers to implementing Common Data Environment (CDE) in the construction phase of BIM-based projects - Abma, Vendie; Nastiti, Aulia Rahma; Ramadhani, Fina (Teknisia, 2024)
The implementation of Building Information Modeling (BIM) has generally been proven to provide changes in the way construction projects are managed and bring long-term benefits in terms of efficiency, cost, and quality. The Common Data Environment (CDE) platform is instrumental in fostering collaboration and coordination in the implementation of BIM. The objective of this study is to examine the barriers to the integration of the CDE in BIM-based construction management during the execution phase of construction projects. To achieve this goal, a survey questionnaire was created to collect feedback on engagement, the main barriers that have been identified through comprehensive literature insights. Primary data was collected from the questionnaire on this project case study with a total of 14 respondents who were directly involved in the project and had access to CDE. The final results show that the main barriers involved are the habits of the conventional system that exists in the company (the company's organizational culture). In order to effect a transformation toward sustainable buildings within the context of a digital construction culture, it is imperative that there be an increased emphasis on encouraging the adoption of this new paradigm. The results of this study will prove to be of the utmost importance for professionals in the construction industry, particularly those in Indonesia, who are in the process of adopting BIM.